Entre “hispanistas” y “pro-yanquis”. El Primer Congreso contra la Intervención Soviética en América Latina, México, mayo de 1954 - Mario Virgilio Santiago Jiménez (Nuevo mundo - Mundos Nuevos, 2017)
Using declassified documents and press, the paper reconstructs the history and development of the First Congress against the Soviet intervention in Latin America, an event that took place in May 1954 in Mexico City, as part of an operation led by the Central Intelligence Agency (CIA) of the United States to overthrow the regime of Juan Jacobo Arbenz in Guatemala. Against the idea of almost perfect machinery, the paper emphasizes the improvisation of the event and the little coordination between actors, highlighting the heterogeneity of anti-communist positions and the need of the CIA to build a network for future operations.